2017
DOI: 10.1126/scitranslmed.aan2966
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoresponsive stem cells to target cancer metastases through biophysical cues

Abstract: Despite decades of effort, little progress has been made to improve the treatment of cancer metastases. To leverage the central role of the mechanoenvironment in cancer metastasis, we present a mechanoresponsive cell system (MRCS) to selectively identify and treat cancer metastases by targeting the specific biophysical cues in the tumor niche in vivo. Our MRCS uses mechanosensitive promoter-driven mesenchymal stem cell (MSC)-based vectors, which selectively home to and target cancer metastases in response to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 71 publications
2
71
0
1
Order By: Relevance
“…Stromal fibroblasts of pancreatic ductal adenocarcinoma tissues in mice promote the suppression of tumor growth upon ganciclovir administration [20,21]. Additionally, Liu et al [2] found that biophysical cues in vivo, specifically matrix stiffness, were potential targets of mesenchymal stem cell-based vectors for cancer treatment, whereas manipulating stroma stiffness may affect the outcomes of cancer treatment. Similarly, we found that when tumor cells were grown on soft PDMS substrates (5.3 kPa), PCM also prepared on the 5.3 kPa substrate led to inhibition of tumor cell survival in response to 5-FU, whereas PCM prepared on a stiffer substrate (46.7 kPa) had no obvious effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stromal fibroblasts of pancreatic ductal adenocarcinoma tissues in mice promote the suppression of tumor growth upon ganciclovir administration [20,21]. Additionally, Liu et al [2] found that biophysical cues in vivo, specifically matrix stiffness, were potential targets of mesenchymal stem cell-based vectors for cancer treatment, whereas manipulating stroma stiffness may affect the outcomes of cancer treatment. Similarly, we found that when tumor cells were grown on soft PDMS substrates (5.3 kPa), PCM also prepared on the 5.3 kPa substrate led to inhibition of tumor cell survival in response to 5-FU, whereas PCM prepared on a stiffer substrate (46.7 kPa) had no obvious effect.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor tissues exhibit increased stiffness compared with normal tissues. Recent evidence has demonstrated that stroma stiffness plays important roles in the resistance of tumors to chemotherapy [1,2]. Within stiff tissues, the distribution of stroma stiffness is often heterogeneous in different regions of the invasive tumor, in which geographically distinct regions display different constituents and architectures of the extracellular matrix [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In esophageal SCC, increased collagen content was associated with chemotherapy resistance via the MAPK and PI3K/AKT pathways [179]. Even at metastatic sites, collagen crosslinking increases tissue stiffness to promote resistance to treatment [180]. Furthermore, increased collagen content was accompanied by increased hyaluronan accumulation, contributing to doxorubicin drug resistance in pancreatic cancer [181].…”
Section: Subtype Of Mmps Associated Collagen Pathological Functions Omentioning
confidence: 99%
“…A growing body of evidence indicates that MSCs activate direct leukocyte-like homing mechanisms with positive tumor tropism in response to adhesion molecules and matrix stiffness. 181 Mechanoresponsive cell systems of the new generation with stiffness sensors can directly deliver antitumor agents to the tumor sites 182 at least in breast and lung cancer. Development of different mechanosensors for a variety of tissues will open a new era in the translational medicine of cancers.…”
Section: Fig 3 Major Mechanosensitive Signaling Pathways In Lineagementioning
confidence: 99%